2012
DOI: 10.1074/mcp.o111.016246
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Multifunctional Tandem Affinity Purification Approach Applicable to Diverse Organisms

Abstract: Determining the localization, binding partners, and secondary modifications of individual proteins is crucial for understanding protein function. Several tags have been constructed for protein localization or purification under either native or denaturing conditions, but few tags permit all three simultaneously. Here, we describe a multifunctional tandem affinity purification (MAP) method that is both highly efficient and enables protein visualization. The MAP tag utilizes affinity tags inserted into an expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…This suggests that BioID may be more amenable to the identification of transient or temporally-regulated interactions than AP-MS from asynchronous cells. We note that, while not addressed here, it is possible to synchronize cells prior to AP-MS [2931] which would allow to enrich interactions present at specific cell cycle stages. For significantly enriched GO terms in common between AP-MS and BioID, such as chromatin organization and response to DNA damage, we observed that different prey proteins contributed to the GO term enrichment (supplementary Figure 5A and B).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that BioID may be more amenable to the identification of transient or temporally-regulated interactions than AP-MS from asynchronous cells. We note that, while not addressed here, it is possible to synchronize cells prior to AP-MS [2931] which would allow to enrich interactions present at specific cell cycle stages. For significantly enriched GO terms in common between AP-MS and BioID, such as chromatin organization and response to DNA damage, we observed that different prey proteins contributed to the GO term enrichment (supplementary Figure 5A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Tandem affinity purification (TAP), multifunctional TAP, or other affinity-based tags can also be used (Rigaut et al. , 1999; Ma et al. , 2012).…”
Section: A Step-by-step Guide To the Identification And Analysis Of Pmentioning
confidence: 99%
“…Although the homology of S-periaxin to other proteins is low, the C-terminal extensions gradually increase the possibility of oligomer formation through the Cys139-Cys139 intermolecular disulfide bond. Various techniques, including yeast two-hybrid screening, Co-IP, glutathione S-transferase pull-down, and the recently developed tandem affinity purification assays, have been used to detect and study protein-protein interactions [11,25,26]. BiFC, which was developed by Hu et al [27], detects weak or otherwise transient protein-protein interactions in vivo.…”
Section: Discussionmentioning
confidence: 99%